Benjamin Franklin unmasked : on the unity of his moral, religious, and political thought - Weinberger, Jerry, 1944- (American political thought., 2005)
"Moral paragon, public servant, founding father; scoundrel, opportunist, womanizing phony: There are many Benjamin Franklins. Now, as we celebrate the tercentenary of Franklin's birth, Jerry Weinberger reveals the Franklin behind the many masks and shows that the real Franklin was far more remarkable than anyone has yet discovered."